2018
DOI: 10.1136/bmjgh-2017-000485
|View full text |Cite
|
Sign up to set email alerts
|

What drives political commitment for nutrition? A review and framework synthesis to inform the United Nations Decade of Action on Nutrition

Abstract: IntroductionGenerating country-level political commitment will be critical to driving forward action throughout the United Nations Decade of Action on Nutrition (2016–2025). In this review of the empirical nutrition policy literature, we ask: what factors generate, sustain and constrain political commitment for nutrition, how and under what circumstances? Our aim is to inform strategic ‘commitment-building’ actions.MethodWe adopted a framework synthesis method and realist review protocol. An initial framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(221 citation statements)
references
References 81 publications
9
189
0
1
Order By: Relevance
“…It refers to both the intention to act (intentionality or willingness) and action itself . Credible and sustained commitment—from political leaders who champion policy initiatives and government officials who coordinate action, to civil society groups who advocate for attention and resources, and ultimately affected community groups and individual citizens—is crucial to driving nutrition policy responses in the long term …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It refers to both the intention to act (intentionality or willingness) and action itself . Credible and sustained commitment—from political leaders who champion policy initiatives and government officials who coordinate action, to civil society groups who advocate for attention and resources, and ultimately affected community groups and individual citizens—is crucial to driving nutrition policy responses in the long term …”
Section: Resultsmentioning
confidence: 99%
“…To further develop and refine these models, we drew from the results of a review of empirical studies on the drivers of political commitment for nutrition conducted by four of the authors (P.B., K.W., H.W., and A.D.) . This involved keyword searches of scholarly databases and institutional websites for research articles and grey literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the reasons behind the implementation gaps were not investigated in this study, they generally include among others the lobbying by food companies opposing recommended policies, the restricted ability or willingness of governments to implement regulations, and the limited pressure from civil society organizations for policy action due to restricted capacity and funding and weak coordination . A recent review identified nutrition actor networks, civil society mobilization, robust data systems, and available evidence among other factors driving political commitment for nutrition irrespective of country context . The Food‐EPI tool and process may hence contribute to create and strengthen several of these factors driving such commitment.…”
Section: Discussionmentioning
confidence: 99%